National survey on image‐guided radiotherapy practice in New Zealand. Issue 2 (26th October 2017) - Padayachee, Jerusha; Loh, Jasmin; Tiong, Albert; Lao, Louis
Abstract: Introduction: This survey aimed to assess the use of image‐guided radiotherapy (IGRT) within New Zealand (NZ) and evaluate the quality of IGRT delivery. Method: All nine centres in NZ were invited to participate in an online survey in November 2015. Questions were asked on type of IGRT technologies available, IGRT use by tumour site and frequency of imaging. In addition, questions were asked in reference to the American Society for Radiation Oncology (ASTRO) White Paper recommendations on safe practice of IGRT. Results: Seven of the nine centres (78%) responded. Kilovoltage cone‐beam CT (CBCT), kilovoltage planar imaging and megavoltage electronic portal imaging were the most commonly used IGRT technologies. CBCT was most frequently used in gynaecology (100%), genitourinary (86%) and head and neck (86%) sites. Despite the availability of similar IGRT technologies, there was significant variation in their application between centres. All centres used online IGRT; however, the frequency of imaging varied across the tumour sites and individual centres. Daily online IGRT use ranged from 43% to 86% across the tumour sites. Overall, there was good compliance by the NZ centres to the White Paper recommendations, with at least 71% reached for each element. However, the compliance rates for the individual centres ranged between 50% and 100%. The most commonly identified barrier to IGRT use was lack of guidelines/education (43%). Conclusion: Image‐guided radiotherapy is widely used in NZ; however, there is a wide variation in its application between centres. Detailed tumour site‐specific, imaging modality‐specific national guidelines will allow standardization of IGRT practices.